Sex differences in HIV-1 persistence and the implications for a cure - Rao, Shringar (Frontiers in Global Women's Health, 2022)
Of the 38 million people currently living with Human Immunodeficiency Virus type-1 (HIV-1), women, especially adolescents and young women, are disproportionally affected by the HIV-1 pandemic. Acquired immunodeficiency syndrome (AIDS) - related illnesses are the leading cause of death in women of reproductive age worldwide. Although combination antiretroviral therapy (cART) can suppress viral replication, cART is not curative due to the presence of a long-lived viral reservoir that persists despite treatment. Biological sex influences the characteristics of the viral reservoir as well as the immune responses to infection, factors that can have a significant impact on the design and quantification of HIV-1 curative interventions in which women are grossly underrepresented. This mini-review will provide an update on the current understanding of the impact of biological sex on the viral reservoir and will discuss the implications of these differences in the context of the development of potential HIV-1 curative strategies, with a focus on the shock and kill approach to an HIV-1 cure. This mini-review will also highlight the current gaps in the knowledge of sex-based differences in HIV-1 persistence and will speculate on approaches to address them to promote the development of more scalable, effective curative approaches for people living with HIV-1.